STUDIES ON THE BIOLOGY OF NEMATOPALAEMON TENUIPES (HENDERSON) IN BOMBAY COAST - Kunju, M M (Indian Journal of Fisheries, 2011)
One of the most conspicuous features of the "dol" net fishery along theMaharashtra coast is the enormous abundance of the small marine palaemonid,Nematopalaemon tenuipes. The only other maritime state where the speciessupports a commercial fishery is Gujarat (Banerji 1966). It is largely a marinespecies capable of penetrating estuarine areas, from where it is often commerciallyexploited, as in the case of the Godavary estuary (Ganapati and Subrahmanyam1966) and the Sunderbans (Kunju 1956, Rajyalakshmi 1966). Thespecies was formerly known as Leander tenuipes {vide Holthuis 1950 for synonymyand Kemp 1917 for identification keys of the different species of thegenus